To call a spade a spade: use of force depriving a people of their right to self-determination as violation of Jus Contra Bellum - Yip, Ka Lok (Journal on the use of force and international law, 2024)
This article argues that a use of force which deprives a self-determination entity ('SDE') of its right to self-determination is prohibited under both Article 2(4) of the UN Charter and customary international law, even if there may not be sufficient practice accepted as law (opinio juris) to establish that such forcible deprivation of an SDE's right to self-determination constitutes an armed attack that entitles the SDE to the right of self-defence. The article also argues that a State's use of force to occupy or subjugate an SDE to permanently prevent an armed attack from emanating from that SDE does not qualify as lawful self-defence in the absence of an actual or imminent armed attack. Furthermore, a State's use of force against attacks emanating from an SDE that could have been averted by the State's relinquishing control over the SDE does not satisfy the necessity requirement to qualify as lawful self-defence.